Ideias que fundamentam a prática pedagógica de professores de ciências da educação de jovens e adultos - Limberger, Karen Martins (2013)
This research, which is about the ideas that underlie the pedagogical practice of science teachers Education for Youth and Adults (EJA) sought to understand how teachers are underpinning, planing and execute lessons in this teaching modality, are heterogeneous classes, encompassing much diversity and specificity. To conduct the survey of the ideas from the teachers, the start point was a semi-structured semi-structured recorded interview, which was later transcribed, and used for the discursive Textual Analysis to analyze the data collected. Based on this information, it was found that EJA Sciences teachers use as a source for class planning literature the regular education textbooks, since the content in the EJA book is integrated structured, which is related as distant from the class reality by EJA teachers. The teachers' planning focuses on conceptual content, trying to relate to it the everyday questions, and try not to have a didactic sequence over the weeks for the failures of students. Additionally, teaching strategies are conducted in a traditional exhibition, but seek to use other ways, as presenting movie pictures, visiting museums, practicing experiments and group works. Teachers also report the realization of continued education through update strategies promoted by the education department, school meeting discussions, and the creation of a study group to discuss about EJA subjects. Thus, this research revealed the fundamental importance of an internal articulation among teachers, school and the education department, in order to work together in search of a education of better quality, since EJA teachers were not capacitated in their initial formation for this kind of teaching, indicating that it is necessary to consider carefully these questions and seek for actions that contribute socially with the students, during the teaching and learning process.